A critical analysis of constraints faced by the urban and peri urban dairy farmers in and around Hyderabad city of Telangana (Indian Journal of Animal Production and Management, 2017)
The present survey was undertaken to analyze the constraints faced by the urban and peri urban dairy  farmers in around Hyderabad city of Telangana. A sample of 100 farmers (50 farmers each from Urban and  Peri urban areas) was selected through simple random sampling technique. The data was analyzed by  Henry Garret’s ranking technique. Twenty constrains were identified in the study. The study indicated that  high cost of fodder and concentrates was perceived as a major problem (with a score of 76.19) followed  by high cost of dairy animals as the second major constraint (with a score of 76.11) and high incidence of  prolapse of uterus in dairy animals ( with a score of 23.09) was a twentieth constraint.
Keywords: Constraints; Telangana; Urban and Peri urban dairy farmers